Evolution of the System of Franchising in Brazil - Lima, Aloisio Soares (2012)
In Brazil there currently has been an increasing interest in entrepreneur franchising and the control over any potential sources of conflict has become a relevant factor to sustain a good, long-term relationship between the two companies involved. The objectives of this paper are to verify the advantages of the franchising system, to examine the satisfaction levels of each entrepreneur in relation to such system, and to demonstrate the differences concerning licensing and franchising legal aspects. The research was carried out in three steps. The data were first collected from this sector, which has recently shown a promising advance in the Brazilian economy. Next, a licensing and franchising system comparison was conducted. Finally, questionnaires were selected and emailed to franchising companies and their holder units. The sampling constituted of 45 franchise granting companies following six distinct segments and by 270 franchise holder units. After having analyzed the data, the characteristics of the relationships between both parties was identified, especially those associated with the brand value, marketing management, intranet communication and satisfaction brought by the investment. A relative association between the franchise holders performance segment and its respective satisfaction level, as well as in relation to the business operational period was observed.